2017
DOI: 10.1097/pcc.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extracorporeal Membrane Oxygenation and Mortality in Pediatric Cardiac Surgery Patients With Genetic Conditions: A Multicenter Analysis*

Abstract: Objective Congenital heart disease is commonly a manifestation of Genetic Conditions (GC). Surgery and/or ECMO were withheld in the past from some patients with GC. We hypothesized that surgical care of children with GC has increased over the last decade but their cardiac ECMO use remains lower and mortality greater. Design Retrospective Cohort Study Setting Patients admitted to the Pediatric Health Information System database ≤18 years old with cardiac surgery during 2003–14. GC identified by ICD9 codes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Previous studies of adult patients after cardiac surgery have not specifically examined DWE, although this was recently examined after pediatric cardiac surgery . We found that DWE occurred in 1.4% of adults undergoing ACHD surgery, similar to the rate of 1.6% in pediatric patients with no known genetic condition after cardiac surgery . As stated previously, a proportion of patients that die without ECMO could possibly have survived if they had been supported with ECMO.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Previous studies of adult patients after cardiac surgery have not specifically examined DWE, although this was recently examined after pediatric cardiac surgery . We found that DWE occurred in 1.4% of adults undergoing ACHD surgery, similar to the rate of 1.6% in pediatric patients with no known genetic condition after cardiac surgery . As stated previously, a proportion of patients that die without ECMO could possibly have survived if they had been supported with ECMO.…”
Section: Discussionsupporting
confidence: 80%
“…Pediatric cardiac surgical programs routinely use extracorporeal membrane oxygenation (ECMO) to rescue surgical patients with cardiopulmonary failure, and predictors of ECMO support in these patients have been well documented . However, predictors of ECMO support in adults after CHD surgery have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations